Links between depression and openness and its facets. (2nd April 2018) - Khoo, Shereen; Simms, Leonard J.
Abstract: Most studies on depression and personality have focused on the role of Neuroticism and Extraversion. Openness is a much less studied trait in this literature, as past studies investigating Openness and depression often have found non‐significant correlations between them. However, past studies mostly have investigated Openness and depression at the domain level and used non‐clinical samples. In the present study, the relationship between depression and Openness at the domain and facet levels was examined in a sample of 266 participants recruited from outpatient psychiatric settings. Findings showed that although the Openness domain was significantly related to depression, it did not account for a significant proportion of unique variance for depression. However, Openness did account for a significant proportion of unique variance for depression at the facet level, even after accounting for sex, age, Neuroticism and Extraversion. Specifically, unique effects emerged for the facets of Aesthetics positively predicting Depression and Values negatively predicting Depression and Anhedonia. Clinical and theoretical implications are discussed. Copyright © 2018 John Wiley & Sons, Ltd.